Сучасна українська химерна проза та жанрові різновиди «темної літератури» - Кобилко, Н. А.; Kobylko, N. A.; ORCID: https://orcid.org/0000-0001-8123-4156 (Проблеми гуманітарних наук. Серія : Філологія. - 2021. - Вип. 47. - С. 93-98, 2021)
Розглянуто основні жанри «темної літератури» та виявлено їх спільні риси з українською химерною прозою, яка посідає чільне місце в сучасному літературному процесі. Сьогодні автори дедалі частіше використовують міфологічні мотиви й сюжети, звертаються до фольклорних образів-символів та елементів народної обрядовості. Наголошено, що найбільшу спорідненість із химерною прозою виявляють магічний реалізм, готичний роман, фентезі, горор і психологічний трилер, які зберігають атмосферу таємничості й ірреальності, частково використовують елементи міфів і фольклору.

The article considers the main genres of “dark literature” and reveals their common features with the Ukrainian bizarre prose, which occupies a prominent place in the modern literary process. Today, authors increasingly use mythological motifs and plots, turn to folklore images-symbols and elements of folk rituals.In Ukraine, the House of Chimeras, founded by the writer V. Granetska and the poet V. Sord, specializes in bizarre genre and author's prose. The cluster of “dark literature” combines a mystical-psychological thriller, horror, detective noir, dark fantasy, magical realism, the latest Ukrainian demonology/mythology, etc.In the works of modern authors there are many features characteristic of the bizarre prose of the second half of the twentieth century, namely: conventionality, sarcasm, grotesqueness, change of tones, unreality, lyricism, philosophical orientation, intellectualism. The novels do not have a clear plot, it contains a confusing story and an unexpected ending, broken chronotope. Artists often depict two parallel worlds, and the main characters are people and mythical creatures, such as an angel, a witch, a peacock, a house, a werewolf, a tortoise, a double-minded chaser, a bird and a jumper, death, one, dream catcher, god, Chaos.Among the analyzed genres of modern “dark literature” the most related to whimsical prose are magical realism, gothic novel, fantasy, horror and psychological thriller, which preserve the atmosphere of mystery and unreality, partially using elements of myths and folklore. All this gives grounds to claim that Ukrainian bizarre prose has evolved and continues to develop.

Рассмотрены основные жанры "темной литературы" и выявлены их общие черты с украинской причудливой прозой, которая занимает ведущее место в современном литературном процессе. Сегодня авторы все чаще используют мифологические мотивы и сюжеты, обращаются к фольклорным образам-символам и элементам народной обрядности. Отмечено, что наибольшее родство с причудливой прозой проявляют магический реализм, готический роман, фэнтези, хоррор и психологический триллер, сохраняющие атмосферу таинственности и ирреальности, частично использующие элементы мифов и фольклора.
Modern Ukrainian chimerical prose and its genre varieties of “dark literature”
Кобилко, Н. Сучасна українська химерна проза та жанрові різновиди «темної літератури» / Кобилко Наталія // Проблеми гуманітарних наук. Серія : Філологія. - 2021. - Вип. 47. - С. 93-98. - DOI: https://doi.org/10.24919/2522-4565.2021.47.12.
Кобилко, Н. (2021). Сучасна химерна проза та жанрові різновиди «темної літератури». Проблеми гуманітарних наук: збірник наукових праць Дрогобицького державного педагогічного університету імені Івана Франка. Серія «Філологія», 47, 93–98. doi: https://doi.org/10.24919/2522-4565.2021.47.12.
Keywords: Мова. Мовознавство. Літературознавство. Language. Linguistics. History and Criticism of Literature. Язык. Языкознание. Литературоведение; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; химерне прозописьмо; whimsical prose writing; причудливая прозопись; магічний реалізм; magical realism; магический реализм; готичний роман; gothic novel; готический роман; фентезі; fantasy; фэнтези; горор; horror; психологічний трилер; psychological thriller; психологический триллер